Provincial Shakespeare performance, 1769-2016: cultural exchange between centre and periphery - Coleman Manktelow, Hannah (2019)
This thesis provides a wide-ranging analysis of Shakespeare performance in the English provinces from the 1769 Shakespeare Jubilee to the 2016 quatercentenary of Shakespeare’s death. Using playbills, programmes, reviews and interviews, I reconstruct over two hundred and fifty years of provincial performance to reveal a complex ecology of cultural exchange between ‘centre’ and ‘periphery’. Chapter 1 considers the factors that cast London as the centre and the English provinces as the periphery of Shakespeare performance from 1769 to 1850. It examines in what ways provincial productions were shaped by this hierarchy, and how they developed their own approaches. Chapter 2 traces connections between the demise of the provincial stock company and the advent of the railway from 1850 to 1900. It explores how technological change increased national connectivity and reconfigured the centre/periphery binary by expanding intra-provincial cultural exchange. Chapter 3 addresses the impact of repertory upon the theatrical hierarchy, and considers the extent to which this altered – and failed to alter – the nature of Shakespeare performance in the provinces. Chapter 4 is centred upon the introduction of government subsidy and the creation of the Royal Shakespeare Company (RSC) in 1961. It examines the RSC as a new Shakespearean authority, before shifting focus to the productions and practices of the Nottingham Playhouse. Chapter 5 uses a micro study of a major 2016 collaboration between the RSC and eleven provincial theatres to examine interactions between cultural centre and periphery in Shakespeare performance up close.